2019
DOI: 10.3847/1538-4357/ab2fdf
|View full text |Cite
|
Sign up to set email alerts
|

Pulsating in Unison at Optical and X-Ray Energies: Simultaneous High Time Resolution Observations of the Transitional Millisecond Pulsar PSR J1023+0038

Abstract: PSR J1023+0038 is the first millisecond pulsar discovered to pulsate in the visible band; such a detection took place when the pulsar was surrounded by an accretion disk and also showed X-ray pulsations. We report on the first high time resolution observational campaign of this transitional pulsar in the disk state, using simultaneous observations in the optical (TNG, NOT, TJO), X-ray (XMM-Newton, NuSTAR, NICER), infrared (GTC) and UV (Swift) bands. Optical and X-ray pulsations were detected simultaneously in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(127 citation statements)
references
References 104 publications
(122 reference statements)
11
116
0
Order By: Relevance
“…A variety of interpretation have been proposed for the complex behaviour during the LMXB state: an enshrouded pulsar (Coti Zelati et al 2014;Takata et al 2014), a pulsar in a propeller state (Papitto et al 2014;, an intermittent propellering radio pulsar (Ertan 2017) or a low accretion rate pulsar from a trapped disc near corotation (D'Angelo & Spruit 2012) (see also Campana & Di Salvo (2018), for a review). Whether the disc shocks with a striped pulsar wind at a few light cylinder radii away from the pulsar, giving rise synchrotron emission producing the optical and X-ray pulses, is a challenging intepretion put forward by Papitto et al (2019) (see also Veledina et al 2019;Campana et al 2019).…”
Section: ;mentioning
confidence: 99%
“…A variety of interpretation have been proposed for the complex behaviour during the LMXB state: an enshrouded pulsar (Coti Zelati et al 2014;Takata et al 2014), a pulsar in a propeller state (Papitto et al 2014;, an intermittent propellering radio pulsar (Ertan 2017) or a low accretion rate pulsar from a trapped disc near corotation (D'Angelo & Spruit 2012) (see also Campana & Di Salvo (2018), for a review). Whether the disc shocks with a striped pulsar wind at a few light cylinder radii away from the pulsar, giving rise synchrotron emission producing the optical and X-ray pulses, is a challenging intepretion put forward by Papitto et al (2019) (see also Veledina et al 2019;Campana et al 2019).…”
Section: ;mentioning
confidence: 99%
“…Interestingly, PSRJ1023+0038 also exhibited optical pulsations during the sub-luminous disk state, which makes it the first millisecond pulsar ever detected in the optical (Ambrosino et al 2017). Papitto et al (2019) argued that the pulsed optical emission originates neither from magnetically channelled accretion nor a rotation-powered pulsar magnetosphere, but synchrotron emission from the intrabinary shock between the pulsar wind and the accretion disk. This would imply that the rotation-powered activity of a pulsar persists in the subluminous disk state.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, there is no known mechanisms able to account for the large pulsed optical luminosity in J1023, involving the accretion of matter onto the NS surface (cyclotron emission falls by a factor 35 Ambrosino et al 2017). Papitto et al (2019) proposed that optical and X-ray pulsations are produced in intra-binary shocks when the relativistic wind of the pulsar interacts with the in-flowing matter close to the light cylinder. In the new physical 1 Technically, nsatmos model is for a cooling NS atmosphere, but is has been shown to describe fairly well also low-level accretion.…”
Section: Pulsations From An Intra-binary Shock In a Shock Emission Scmentioning
confidence: 99%
“…Veledina et al (2019) suggested instead that during the low mode, matter is accreted onto the NS. Papitto et al (2019) suggested that flares might come from a complete enshrouding of the pulsar. At variance with the previous scenario, it seems natural here to include flare mode data into the spectral fits, to investigate this possibility.…”
Section: Pulsations From An Intra-binary Shock In a Shock Emission Scmentioning
confidence: 99%
See 1 more Smart Citation